COOPERATION AS A FORM OF COMMUNICATION BETWEEN PARENTS AND PRE-SCHOOL TEACHERS - Liepa-Liepiņa, Lelde; Vronska, Nataļja (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Communication is a continuous process. Communication connects people. It is verbal communication, non-verbal or gesture-mimic communication and writing, when we express our opinion in writing. Communication has a management function that is closely linked to the management processes at the pre-school institution. Communication improves the flow of information between pre-school teachers and parents. Accuracy of information is an important aspect of communication, because the information transferred to parents is researched, analysed, interpreted and preserved. Therefore, pre-school teachers need to spend time working on information that is then accurately formulated for parents. An important aspect is the way information is communicated. It is important that communication between pre-school teachers and parents is constructive, open and honest. The article aim is to analyse and evaluate the scientific literature and other sources of communication and cooperation, complete a survey to find pre-school parents' preferred forms of cooperation with pre-school teachers.